Vintage Madhya Pradesh - Rag, Pankaj (Bhopal, 2005)
Set in a timeless frame, photographs of 'Vintage Madhya Pradesh' attempt to portray the region, today known as Madhya Pradesh, as it was from the late 19th century to the early 1960s.
Keywords: Madhya Pradesh-Old photographs